River water infiltration enhances denitrification efficiency in riparian groundwater. (1st March 2018) - Trauth, Nico; Musolff, Andreas; Knöller, Kay; Kaden, Ute S.; Keller, Toralf; Werban, Ulrike; Fleckenstein, Jan H.
Abstract: Nitrate contamination in ground- and surface water is a persistent problem in countries with intense agriculture. The transition zone between rivers and their riparian aquifers, where river water and groundwater interact, may play an important role in mediating nitrate exports, as it can facilitate intensive denitrification, which permanently removes nitrate from the aquatic system. However, the in-situ factors controlling riparian denitrification are not fully understood, as they are often strongly linked and their effects superimpose each other. In this study, we present the evaluation of hydrochemical and isotopic data from a 2-year sampling period of river water and groundwater in the riparian zone along a 3rd order river in Central Germany. Based on bi- and multivariate statistics (Spearman's rank correlation and partial least squares regression) we can show, that highest rates for oxygen consumption and denitrification in the riparian aquifer occur where the fraction of infiltrated river water and at the same time groundwater temperature, are high. River discharge and depth to groundwater are additional explanatory variables for those reaction rates, but of minor importance. Our data and analyses suggest that at locations in the riparian aquifer, which show significant river water infiltration, heterotrophic microbial reactions in the riparian zone may be fueled by bioavailable organic carbon derived from the river water. We conclude that interactions between rivers and riparian groundwater are likely to be a key control of nitrate removal and should be considered as a measure to mitigate high nitrate exports from agricultural catchments. Graphical abstract: Highlights: Hydrochemical and isotopic data of 2-year sampling period in a riparian zone. Temperature can explain 67.8% of the variance in DO and 66.2% in δ 15 N. The higher the river water content in groundwater the higher is δ 15 N enrichment. Reactions depend on bioavailable carbon delivered by infiltrating river water.